ANALISIS PENDEKATAN RELIGIUSITAS DALAM PELAKSANAAN PROGRAM PEMBINAAN AGAMA ISLAM NARAPIDANA DI LAPAS NARKOTIKA KELAS IIA YOGYAKARTA - Nur Said Avandi; Andi Kurniawan (Jurnal Komunikasi Hukum, 2025)
This study aims to analyze the religiosity approach in the implementation of Islamic religious training programs for inmates at the Class IIA Narcotics Prison in Yogyakarta. The main focus is to explore how the religiosity approach is applied in the training process and the obstacles encountered during its implementation. This research uses a qualitative method with a descriptive approach, where data is collected through interviews, observations, and document analysis. The training program conducted through the At-Tawwabin Islamic Boarding School has been shown to play a significant role in enhancing inmates' religiosity, including in the dimensions of belief, worship, experience, knowledge, and practice. However, there are challenges in the implementation, particularly regarding the varying motivation of inmates in participating in the training program. The findings are expected to contribute to improving the effectiveness of Islamic religious training programs at the Class IIA Narcotics Prison in Yogyakarta and provide input for stakeholders in managing religiosity-based training.